Cascading effects of fire retardant on plant–microbe interactions, community composition, and invasion. Issue 4 (June 2016) - Marshall, Abigail; Waller, Lauren; Lekberg, Ylva
Abstract: Climate change, historical fire suppression, and a rise in human movements in urban‐forest boundaries have resulted in an increased use of long‐term fire retardant (LTFR). While LTFR is an effective fire‐fighting tool, it contains high concentrations of nitrogen and phosphorus, and little is known about how this nutrient pulse affects terrestrial ecosystems. We used field surveys and greenhouse experiments to quantify effects of LTFR on plant productivity, community composition, and plant interactions with the ubiquitous root symbiont arbuscular mycorrhizal fungi (AMF). In the field, LTFR applications were associated with persistent shifts in plant communities toward exotic annuals with little or no dependency of AMF. Plants exposed to LTFR were less colonized by AMF, both in field surveys and in the greenhouse, and this was most likely due to the substantial and persistent increase in soil available phosphorus. All plants grew bigger with LTFR in the greenhouse, but the invasive annual cheatgrass ( Bromus tectorum ) benefitted most. While LTFR can control fires, it may cause long‐term changes in soil nutrient availabilities, disrupt plant interactions with beneficial soil microbes, and exasperate invasion by some exotic plants.